Handbook of New Institutional Economics - Ménard, Claude (Springer, 2008)
"This Open Access Handbook of New Institutional Economics (NIE) is a comprehensive reference work providing a unique and timely overview of recent developments and broad orientations in institutional analysis. This second edition has been thoroughly updated and extended, including 21 new chapters on political and legal institutions, organizations and contracts, regulation, culture, methodology and institutional change. Chapters have been written by highly respected scientists in the field, among them Ronald Coase, Douglass North, Elinor Ostrom, Oliver Williamson and Roger Myerson, and most recently Joel Mokyr — all Nobel recipients, as well as by numerous other foremost NIE specialists at the frontier of NIE research. This Handbook gives students and young researchers an introduction to the topic and offers all scholars a reference book for their research. It will also be of interest to economists, political scientists, legal scholars, management specialists, sociologists, and others wishing to learn more about these important subjects and gain insight into progress made by institutionalists from other disciplines."